Apoptosis in Prostate Carcinoma Tissue: The Role of Caspase-3, Caspase-1, and Alkaline DNase Activity: Apoptosis in Prostate Carcinoma Tissue - Klisic, Aleksandra (Journal of Medical Biochemistry, 2025)
Background and Aim: Prostate glandular tissue maintains a delicate balance between cellular proliferation and programmed cell death (apoptosis), ensuring the preservation of normal glandular architecture in healthy individuals. Disruption of this equilibrium—whether due to excessive proliferation or impaired apoptotic mechanisms—can contribute to the initiation and progression of prostate cancer. The objective of this study was to evaluate the expression and activity of Caspase-3, Caspase-1, and Alkaline Deoxyribonuclease (DNase) in prostate cancer tissue and tumor-adjacent tissue, in comparison to clinically healthy prostate tissue. The aim was to determine whether alterations in these parameters could serve as early biomarkers for the transformation of surrounding tissue into a precancerous phenotype. Methods: The concentration of Caspase-3 and Caspase-1, as well as the activity of alkaline DNase, were examined in prostate tissue samples, including cancerous tissue, adjacent tissue near the tumor, and surrounding healthy tissue. Results: The results revealed a significant reduction in Caspase-3 levels in cancerous tissue (p < 0.05), with an even more pronounced decrease in the adjacent peritumoral tissue (p < 0.05). In contrast, Caspase-1 levels were markedly elevated in both cancerous tissue (p < 0.00001) and the surrounding non-malignant peritumoral tissue (p< 0.0005). Similarly, Alkaline DNase activity (both total and specific) was significantly increased in cancerous tissue (p < 0.00001), with a moderate but statistically significant elevation in the tumor-adjacent tissue (p < 0.000017) compared to control tissue. Conclusion: These findings suggest a disruption in the interplay between Caspase-3 and Alkaline DNase, potentially as a consequence of necrotic processes or enzyme release from inhibitory complexes. Furthermore, the increased expression of Caspase-1 implies that inflammatory responses may play a role in tumorigenesis.